Peran Komunikasi Dalam Keluarga Kristen Berdasarkan Ulangan 6:7 - Benyamin Telnoni (Sekolah Tinggi Teologi Real Batam, 2020)
Through this article, the author attempts to describe the crucial role of communication in the family based on Deuteronomy 6: 7. Damage to family relationships: husband and wife, parent-child due to stagnant communication between family members. According to the Indonesian Family Home Counselor and Trainer (RKI) that 70% of husband and wife problems are due to communication failures. Even the Head of Prosperous Family and Family Empowerment (KSPK) in Media Indonesia revealed that poor communication between parents and children can result in juvenile delinquency. This means that communication has a very important role in the Christian family. Good or bad a family is determined by how to communicate with family members because effective communication can help prevent problems in the family. Good communication can help parents to prepare the best path for the child's future, including in directing their children to achieve their desired goals. Text analysis of Deuteronomy 6:7 shows that communication between families plays a central role in bringing harmonious and open family to one another. The purpose of this paper is to answer all the problems regarding the role of communication in the Christian family and in review from Deuteronomy 6: 7. The method used in this paper is the method of studying literature and library research.